Estudio morfológico comparado de Verrucaria maura y V. amphibia en la Costa Vasca - Renobales Scheifler, Gustavo; Noya, Rosario (Universidad de Málaga, Servicio de Publicaciones, 1991)
Se estudia la variabilidad que presentan las poblaciones de Verrucaria maura y V. amphibia de la costa vasca. Aparte de las formas típicas, se reconocen tres fenotipos diferentes, uno de ellos perteneciente a V. amphibia y los otros dos a V. mama. La principal variabilidad que presenta V. mania se relaciona con la altura a la que se encuentra en la costa.Los caracteres más útiles para la discriminación entre las dos especies son la forma del borde del talo y la anchura de las esporas

Morphological variability in Verrucaria mania and V. amphibia is studied from populations living in the Basque Coast (N-Spain). Five different phenotypes are recognized, two of them belonging to V. amphibia (typical and type « a» 1), while the other three belong to V. maura (typical and types «m»1 and «m»2). Their morphology is summarized and compared in tables 1 and 2. Their macroscopic habit is shown in figs. 1-5.The most constant characters, hence the most suitable to distinguish between the two species, are the border of the thallus, wich is abrupt and without hypothallus in V. amphibia while it is thin and has a clear hypothallus in V. mania, and the size of spores, constantly broader in V. matra. All other morphological characters are far more variable and less useful for discrimination. The main variability found in V. mania is related with the relative level occupied by the specimens in the coast, while that found in V. amphibia is probably related with the degree of insolation.One of the phenotypes of V. mania, t. «m»2, is in uncertain posit ion for the momem, as it appears to be intermediate between the two species.